Management of patients with venous thromboembolism and a high recurrence risk estimated by the Vienna Prediction Model: a prospective cohort study - Hana Šinkovec; Paul A. Kyrle; Lisbeth Eischer; Paul Gressenberger; Thomas Gary; Marianne Brodmann; Georg Heinze; Sabine Eichinger (Research and Practice in Thrombosis and Haemostasis)
Background: The Vienna Prediction Model (VPM) identifies patients with a first unprovoked deep vein thrombosis of the leg and/or pulmonary embolism who have a low recurrence risk and may, therefore, not benefit from extended-phase anticoagulation. Objectives: The aim of this study was to evaluate patients with a predicted high risk of recurrent venous thromboembolism (VTE). Methods and Results: We prospectively followed 266 patients in whom the VPM had predicted a recurrence risk of more than 5.5% at 1 year for a median of 13.5 months. Their median age was 56 years, and 96% were men. After the VPM risk assessment, 196 patients restarted anticoagulation. While on anticoagulation, none of the patients experienced recurrent VTE, whereas 4 patients had nonmajor clinically relevant bleeding (absolute bleeding rate, 1.8 [95% CI, 0.5-4.5] events per 100 patient-years). Seventy patients were left untreated after VPM risk assessment for various reasons. Among patients not using anticoagulation, 15 had recurrence (absolute recurrence rate, 18.1 [95% CI, 10.1, 29.9] events per 100 person-years). According to the extended Kaplan–Meier analysis, the probability of VTE recurrence in patients not on anticoagulation was 10.1% and 17.9% at 6 and 12 months after VPM risk assessment, respectively. Conclusion: Anticoagulant therapy is effective and safe in patients with an unprovoked VTE, in whom the VPM had predicted a high risk of recurrent VTE. If these patients are left untreated, the risk of recurrence is high.